Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada Gdr Mart Di Panyalain - Mirawati Mirawati; Roni Wahyu Saputra; Rahmad Ade Putra (MABIS: Jurnal Manajemen Bisnis Syariah, 2022)
The issue of the thesis was whether the quality of services and prices affected consumer satisfaction at the GDR mart in profit. The purpose of this study is to find out if the quality of services and prices have any effect on consumer satisfaction at GDR mart in pranyalaian. The research that the authors are doing is using a quantitative method with a descriptive approach. The data-collection technique USES a questionnaire to get the number of respondents with a sample of 97. Data analysis techniques using linear berganda regression analysis treated using version 22. Studies have shown that (1) quality variables of service affect consumer satisfaction (2) price variables affect consumer satisfaction. (3) simultaneous variables of service quality and price affect consumer satisfaction at the GDR mart in pranyalaian.